Features of Translation and Adaptation of Nuclear Energy Terminology in the Azerbaijani Language: Linguistic and Scientific Aspects - Sadigova, Nigar (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2025)
This article examines the translation and adaptation of nuclear energy terminology into the Azerbaijani language from both linguistic and scientific perspectives. It discusses the challenges faced in accurately conveying complex nuclear terms, how dominant source languages (notably English and Russian) influence Azerbaijani nuclear vocabulary and the strategies employed for semantic and terminological adaptation. Issues of standardisation are explored, highlighting efforts by Azerbaijani institutions to unify technical terminology and ensure clear communication. Real examples of Azerbaijani nuclear energy terms are provided to illustrate how terms are translated or coined, such as nüvə reaktoru («nuclear reactor») and atom elektrik stansiyası («nuclear power plant»). The article draws on scholarly sources, glossaries (e.g., IAEA standards), and language policy documents to underscore the importance of consistent, accurate terminology in scientific discourse and national language development. The findings show that while historical Russian influence and modern English borrowings shape the Azerbaijani nuclear lexicon, deliberate adaptation and standardisation efforts are helping to harmonise terminology for effective scientific communication.